Legal Deposit on the Internet: A Case Study - Henriksen, Birgit N. (LIBER Quarterly: The Journal of the Association of European Research Libraries, 1999)
The subject of my paper will be legal deposit on the Internet in Denmark. I will be telling you about the system supporting the legislation, rather than the legislation itself. The system has been developed over the last one and a half years at The Royal Library and is still under development.